Trajectories of dispensed prescription opioids among beneficiaries enrolled in a Medicaid controlled substance “lock-in” program - Naumann, Rebecca B. (Pharmacoepidemiol Drug Saf, 2018)
PURPOSE: “Lock-in” programs (LIPs) are used by health insurers to address potential substance (e.g., opioid) misuse among beneficiaries. We sought to (1) examine heterogeneity in trajectories of dispensed opioids (in terms of average daily morphine milligram equivalents (MMEs)) over time: prior to, during, and following release from a LIP; and (2) assess associations between trajectory patterns and beneficiary characteristics. METHODS: Medicaid claims were linked to Prescription Drug Monitoring Program records for a cohort of beneficiaries enrolled in the North Carolina Medicaid LIP (n=2,701). Using latent class growth analyses, we estimated trajectories of average daily MMEs of opioids dispensed to beneficiaries across specific time periods of interest. RESULTS: Five trajectory patterns appeared to sufficiently describe underlying heterogeneity. Starting values and slopes varied across the five trajectory groups, which followed these overall patterns: (1) start at a high level of MMEs, end at a high level of MMEs (13.1% of cohort); (2) start medium, end medium (13.2%); (3) start medium, end low (21.5%); (4) start low, end medium (22.6%); and (5) start low, end low (29.6%). We observed strong associations between patterns and beneficiaries’ demographics, substance use-related characteristics, comorbid conditions, and healthcare utilization. CONCLUSIONS: In its current form, the Medicaid “lock-in” program (LIP) appeared to have limited impact on beneficiaries’ opioid trajectories. However, strong associations between trajectory patterns and beneficiary characteristics provide insight into potential LIP design modifications that might improve program impact (e.g., LIP integration of substance use disorder assessment and referral to treatment, assessment and support for alternate pain therapies).